2001
DOI: 10.1054/bjoc.2001.2149
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study with pegylated liposomal doxorubicin for advanced or unresectable hepatocellular carcinoma

Abstract: SummaryWe performed a pilot-study on pegylated liposomal doxorubicin (PLD) for advanced hepatocellular carcinoma. Seventeen patients received 40 mg/m 2 PLD intravenously every 4 weeks. A clinical benefit response was achieved in 50% (complete remission 7%, minor remission 7%, stable disease 36%). Toxicities were moderate. In view of these encouraging findings, further studies appear warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 26 publications
(23 reference statements)
0
14
0
1
Order By: Relevance
“…The difficulty in relying on response rate as a marker of activity was further illustrated by Hong and Tseng (2003): despite 10% of patients responding to treatment and a further 33% achieving stable disease, the median survival was only 3 months. A favourable toxicity profile has been consistent across all the HCC studies (Halm et al, 2000;Ruff et al, 2001;Schmidinger et al, 2001;Miller et al, 2002;Hong and Tseng, 2003). We found few grade 3 -4 toxicities and notably none involving palmar-plantar erythrodysaesthesia, a dose-limiting toxicity seen in early studies along with stomatitis and neutropaenia (Muggia et al, 1997;Ranson et al, 1997).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The difficulty in relying on response rate as a marker of activity was further illustrated by Hong and Tseng (2003): despite 10% of patients responding to treatment and a further 33% achieving stable disease, the median survival was only 3 months. A favourable toxicity profile has been consistent across all the HCC studies (Halm et al, 2000;Ruff et al, 2001;Schmidinger et al, 2001;Miller et al, 2002;Hong and Tseng, 2003). We found few grade 3 -4 toxicities and notably none involving palmar-plantar erythrodysaesthesia, a dose-limiting toxicity seen in early studies along with stomatitis and neutropaenia (Muggia et al, 1997;Ranson et al, 1997).…”
Section: Discussionmentioning
confidence: 59%
“…A number of studies contemporary to ours (see Table 3) have shown, at best, response rates of 10 -17% (Ruff et al, 2001;Schmidinger et al, 2001;Hong and Tseng, 2003). Two studies, as in our case, revealed no responses: in the first, no objective responses were seen in 16 patients receiving 30 -40 mg m À2 three-weekly.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the midst of systemic treatment modalities for advanced HCC, doxorubicin (C 27 H 29 NO 11 ·HCl; 579.99 Da) has been the one most extensively investigated for HCC treatment [9,10,11,12,13]; nevertheless, systemic doxorubicin has not turned out to be a standard treatment care for HCC owing to its severe systemic toxicity. It is in general consensus that targeting drugs specifically to the tumor site may play role in navigating their undesirable manifestations.…”
Section: Nanodoxorubicinmentioning
confidence: 99%
“…Objective responses to doxorubicin have generally been about 10% with an associated short median survival. [35][36][37][38][39][40] Limited data from trials with epirubicin suggest better response rates but not necessarily longer survival. 41,42 A variety of phase II studies with an anthracycline combined with another agent have not led to a consistent improvement in outcome compared to single-agent studies.…”
Section: Systemic Treatmentmentioning
confidence: 99%